Acute Disseminated Melioidosis Presenting with Septic Arthritis and Diffuse Pulmonary Consolidation in an Otherwise Healthy Adult: A Case Report - Hai Sherng Lee; Abdul Azeez Ahamed Riyaaz; Seng Hong Yeoh (University Library System, University of Pittsburgh, 2015)
Background: Melioidosis is an infectious disease caused by Burkholderia pseudomallei. It is most prevalent in South-East Asia, northern Australia, and the Indian subcontinent. Septic arthritis is a rare manifestation of melioidosis. Melioidosis is usually found in patients with diabetes, heavy alcohol use, or chronic lung disease. Results: We report a case of melioidosis in an otherwise healthy 44-year-old male, who presented with acute painful left knee swelling, high-grade fever associated with chills, rigors and night sweats, and a productive cough. Examination revealed active synovitis with effusion involving his left knee, ankle and elbow joints and scattered crackles over both lung fields. Chest X-ray showed diffuse pulmonary consolidation. Abdominal ultrasound showed splenic micro-abscesses. The diagnosis was made based on a positive blood culture for Burkholderia pseudomallei. He was started on appropriate antibiotics and responded well, becoming afebrile after 48 hours, while his joint effusions disappeared after one week. A repeat chest X-ray after two weeks of intensive antibiotic therapy showed marked improvement. At the time of writing, he was under uneventful outpatient follow-up and still had 12 weeks to complete his course of antibiotics. Conclusion: Septic arthritis only occurs in 4% of patients with melioidosis. When there is diffuse pulmonary involvement, melioidosis may mimic disseminated tuberculosis, other acute disseminated or focal sepsis syndromes, and systemic vasculitis syndromes. This case is relevant for medical literature as melioidosis is emerging and is expanding its known territories worldwide. It should be considered early in the differential diagnoses of patients presenting with constitutional symptoms in endemic areas, so that treatment can be started early to reduce its high mortality and morbidity.